Keadilan Restoratif dalam Tindak Pidana Ringan di Masa Pandemi Covid-19 - I Gusti Ayu Sukrisma Dewi; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2021)
At the time of the Covid-19 pandemic, various activities were suspended in terms of education, tourism, companies, politics, and the resolution of a case that caused a crowd or crowd. Where to minimize the spread of COVID-19 in resolving a minor problem, it can be done through Restorative Justice. The purpose of this study is to analyze the legal arrangements regarding restorative justice in minor crimes during the covid-19 pandemic and criminal sanctions against minor crimes based on restorative justice. This research is a normative legal research using primary and secondary legal sources. Data collection techniques are carried out to obtain the required legal materials through recording and documentation studies. Then, the legal materials are processed using interpretation analysis. The results of the study reveal that the regulation of restorative justice in minor crimes during the covid-19 pandemic is very necessary to regulate criminal sanctions against minor crimes based on restorative justice.